WHAT DRIVES LECTURERS’ COMMITMENT? EXAMINING THE ROLES OF CULTURE, SUPPORT, AND ENGAGEMENT IN PRIVATE UNIVERSITIES - Syahsudarmi, Siti; Juniarti, Atty; Fatkhurahman, Fatkhurahman; Novita, Novita; Norawati, Suarni (Faculty of Economic and Business, University of Pasundan, 2026)
Lecturer commitment plays a vital role in the sustainability and performance of private universities. This study investigates how organizational culture and organizational support drive lecturers’ commitment, with work engagement serving as a key explanatory mechanism. A strong organizational culture fosters shared values and behaviors aligned with institutional goals, while organizational support enhances lecturers’ sense of recognition and professional well-being, thereby strengthening engagement in academic responsibilities. Using a quantitative survey of 250 lecturers from private universities in Riau, data were collected through structured questionnaires and analyzed using Structural Equation Modeling (SEM). The results indicate that organizational culture and organizational support have significant positive effects on lecturers’ commitment, both directly and indirectly through work engagement. These findings highlight the importance of cultivating supportive and adaptive organizational environments to enhance lecturer commitment and improve institutional performance.